Biochemical and Haematological Study in Rats Exposed to Cadmium Chloride in Drinking Water: HanaaA.A and Bara N.AL-Ekelly, - A., Hanaa A. (The Iraqi Journal of Veterinary Medicine, 2007)
The objective of this study was investigate the Physiological effect ofdifferent concentrations of cadmium chloride in drinking water on somebiochemical and haematological parameters of male rats. Animals in thisexperiment were randomly divided into four equal groups and treated for 15weeks as follows : Rats in control group were offered ordinary tap water ,while animal in M1 , M2 , and M3 were received 10 , 20 , 30 ppm Cdcl2 indrinking water, respectively. The activity of Alanine aminotransferase(ALP), Aspartate aminotrasferase (AST) and alkaline phosphatase (ALP) inserum were measured. Further mor, hemoglobin concentration (Hb) andwhite blood cells count (WBCs) were detected. The result revealed thataddition of cadmium chloride in different concentrations in drinking watercaused a significant increase in activity of serum of ALT in treated group(M1 , M2 , M3 ) as compound with control. Within the time the activity ofserum AST was significantly increased in three treated group as comparedwith pretreatment period. On the other hand , significant increase in serumALP concentration were show in both M1 and M3 treated groups at 12th and15th week of the treatment as compared with control group. Significantdecrease in haemoglobin concentration were observed in M1 , M2 , M3 from9th week to the end of experiment comparing to control. While cadmiumchloride treatment caused significant increase in total white blood cells countin treated groups as compared with control group. On Conclusion, it seemslikely that exposure of male rats to cadmium chloride at level above thepermissive one had induced clear biochemical and haematological changes.